STUDY OF PERFORMANCE ASSESSMENT EFFECTIVENESS ON HUMAN RESOURCES GOVERNMENT PUBLIC DEPARTMENT IN JAKARTA - Sudiatmoko Sudiatmoko (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
Anticipatory action on the various changes that occur is an action that cannot be bargained to be done immediately. The changes are larger, more diverse, and almost certainly, and are ongoing, including changes in the organization's management system, especially human resource management. The success of an organization, both private and governmental organizations in achieving its goals is largely determined by anticipatory measures to counteract the adverse effects of the change. This research was conducted at Jakarta Population Department. Specifically, the object of research took place in five tribal areas of the Department of Population, namely: Population Office of West Jakarta Municipality, Central Jakarta Population Subdistrict, East Jakarta Population SubDepartment, South Jakarta Population Duty Sub-Office, and Sub-Province Population of North Kotamadya .The results of this study are: The effectiveness aspects of the performance evaluation that are declared effective is the relevance factor. While that is not effective is the sensitivity, reliability, acceptability, and practicality. Very ineffective is the feedback aspect to the results of the performance evaluation of employees. The existence of the same perception among assessors, and priceless relating to the condition of effectiveness of performance evaluation implementation. This means that the assessor, and the valuable agree that there is a suitability of the aspects of effectiveness in the implementation of its performance evaluation in the DKI Jakarta Population Agency. Policies that can be taken to fix the implementation of performance appraisal of human resources in the organization environment of DKI Jakarta Population Department in order to have high effectiveness, and able to provide input for Jakarta Population Agency organization, among others: feedback factor, sensitivity factor, practicality factor, factors of acceptability, factors of control, and relevance factors